Library's patron behaviour: How library staffs cope with it? / Nur Aliah Zainal, Nur Athirah Hanani Jailani and Noor Farahain Abdul Razak - Zainal, Nur Aliah; Jailani, Nur Athirah Hanani; Abdul Razak, Noor Farahain (Faculty of Information Management, 2015)
Do you remember how the first time you visit the library? Do you recall how you adapt with the new ambience while looking for the information you need? How do you react and cope with all the services and facilities serve in the library? Do you aware that library patron's behavior can affect the librarian to achieve the library's objectives? Based on Jordan P. (1974) , the librarians need to achieve specific objectives but the behavior of the library user's and staffs become the barrier to fulfill the objectives. The research or investigation of patron's behavior cannot be done by observations alone. As an example, the assumptions of a boy is sleeping is not true for a boy who is thinking hard for his problem. It may look simple but sometimes it can be more complicated. The user and patron are the essential element of the library and the librarian should be empathetic and understand their users and have to control many types of user's. However, some of the users have some problems regarding their attitude and it becomes some sort of challenges for the librarians to handle it.